First Report of Achlya oblongata Infection in Freshwater-Reared Asian Seabass Lates calcarifer - Lau, Lik Ming; Kishio, Hatai; Hanako, Fukano; Osamu, Kurata (American Fisheries Society, 2018)
In September 2014, a freshwater oomycete was first isolated from Asian Seabass Lates calcarifer fry that were reared in freshwater at a fish hatchery in Sabah, Malaysia. A fungal strain was isolated from infected fry by using glucose yeast extract (GY) agar. From morphological identification, the strain belonged to the genus Achlya based on the mode of zoospore release. Molecular phylogenetic analysis of the internal transcribed spacer region sequences from the strain showed high similarity (99–100%) to Achlya oblongata. The isolate was able to grow on GY agar incubated at 15–35°C, in GY broth adjusted to pH 3.0–11.0, and in up to 1.0% NaCl. This is the first report of Achlya infection in freshwater-reared Asian Seabass in Malaysia.